2014
DOI: 10.3390/ijms150711275
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Modulate Inflammatory Cytokines after Spinal Cord Injury in Rat

Abstract: Transplantation of mesenchymal stem cells (MSC) improves functional recovery in experimental models of spinal cord injury (SCI); however, the mechanisms underlying this effect are not completely understood. We investigated the effect of intrathecal implantation of human MSC on functional recovery, astrogliosis and levels of inflammatory cytokines in rats using balloon-induced spinal cord compression lesions. Transplanted cells did not survive at the lesion site of the spinal cord; however, functional recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 38 publications
9
87
0
Order By: Relevance
“…The beneficial effects of MSCs on long-term functional recovery from spinal cord injury can be seen up to 6 months 57 or 1 year after administration. 58 However, there is evidence that MSCs survival is low at 2 weeks after injection, 36,59,60 in agreement with the present study showing evidence of transplanted MSCs survival in two out of six animals at 2 weeks. Immunosuppression may enhance MSCs survival, 61 and could be used in future experiments examining longer-term effects of BDNFMSCs transplantation.…”
Section: Beneficial Effects Of Mscssupporting
confidence: 81%
“…The beneficial effects of MSCs on long-term functional recovery from spinal cord injury can be seen up to 6 months 57 or 1 year after administration. 58 However, there is evidence that MSCs survival is low at 2 weeks after injection, 36,59,60 in agreement with the present study showing evidence of transplanted MSCs survival in two out of six animals at 2 weeks. Immunosuppression may enhance MSCs survival, 61 and could be used in future experiments examining longer-term effects of BDNFMSCs transplantation.…”
Section: Beneficial Effects Of Mscssupporting
confidence: 81%
“…Early intravenous delivery of MSC attenuates injury by regulating inflammation in SCI [43] and traumatic brain injury (TBI) [44][45][46]. Additionally, MSC transplantation can reduce the levels of proinflammatory cytokines, such as TNF-α and IL-1 [11,47], and inhibit NFκB signaling [12,48,49]. Moreover, MSCs are capable of switching microglia from a proinflammatory M1 phenotype towards an anti-inflammatory M2 phenotype in vitro [13] and in SCI models [50].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs promote tissue repair mainly by inhibiting inflammation and activating endogenous repair mechanisms [9,10]. Previous studies demonstrated that MSCs reduce inflammatory cytokine (TNFα, IL-1, IL-6) levels [11] and inhibit NFκB activation under inflammatory conditions [12]. Additionally, MSCs are capable of directing stimulated macrophages from a proinflammatory M1 phenotype to an anti-inflammatory M2 phenotype [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been demonstrated to promote axonal regeneration and suppress demyelination [100] . Several different studies in rat models found that MSCs induce nerve regeneration, modulate the production of inflammatory cytokines such as TNF-α and IL-6 and reduce myeloperoxidase activity [101][102][103][104][105] . Menezes et al [106] hypothesized that laminin may play a pivotal role in neuron and axon preservation and regeneration after finding deposits of the glycoprotein on the lesion site …”
Section: Resultsmentioning
confidence: 99%